Can cold-season macrophytes at the senescence stage improve nitrogen removal in integrated constructed wetland systems treating low carbon/nitrogen effluent?. (October 2018) - Zhao, Dehua; Zhang, Miao; Liu, Zhe; Sheng, Jing; An, Shuqing
Graphical abstract: Highlights: The macrophyte configuration improves the N removal in the final effluent of SP-BCW. High COD water in the SP should be pumped to the BCW in early decomposition stages. Cold-season macrophytes are recommended in CWs for secondary effluents from WWTPs. Abstract: Cold-season macrophytes were configured in a system of stabilization ponds (SPs) and batch operation constructed wetlands (BCWs) to supply a carbon source for low carbon/nitrogen (C/N) effluent in spring and summer without generating secondary pollution during the decomposition process. For eutrophic water, the macrophyte configuration increased the average removal efficiency (RE) from 41.6% to 68.6% and from 70.2% to 83.7% for NO3 − -N and TN in the final BCW effluent, respectively, with the concentrations decreasing from 3.08 mg/L to 1.04 mg/L and from 4.94 mg/L to 3.12 mg/L, respectively. In the early decomposition stages, the RE and concentrations were 82.9% and 0.53 mg/L and 89.4% and 2.38 mg/L for NO3 − -N and TN, respectively. Thus, cold-season macrophytes can improve N removal in SP-BCW systems at the senescence stage, especially at the early decomposition stage.